2020
DOI: 10.3390/agronomy10030420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pterocladia capillacea Seaweed Extracts on Growth Parameters and Biochemical Constituents of Jew’s Mallow

Abstract: We performed field experiments to evaluate the influence of two extraction treatments, seaweed (Pterocladia capillacea S.G. Gmelin) water extraction (WE) and ultrasound-assisted water extraction (USWE) at three concentrations (5%, 10%, and 15%), as well as control NPK traditional mineral fertilizer on the growth, yield, minerals, and antioxidants of Jew’s Mallow (Corchorus olitorius L.) during the two seasons of 2016 and 2017 in Egypt. Plant height, number of leaves, and fresh weight of WE10 treatment were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…Seaweed extracts are amongst the most commonly utilized important sustainable biostimulants [4]. The employment of seaweed extracts as biostimulants in agricultural practices is very ancient, having been in use since early plant breeding [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Seaweed extracts are amongst the most commonly utilized important sustainable biostimulants [4]. The employment of seaweed extracts as biostimulants in agricultural practices is very ancient, having been in use since early plant breeding [3].…”
Section: Introductionmentioning
confidence: 99%
“…The positive impacts of seaweed extracts as plant biostimulants have been reported in the literature. Some of the most frequently used extracts are reported to be Pterocladia capillacea [4], Ascophyllum nodosum [16], Ecklonia maxima, Sargassum spp. [17], Ulva lactuca, Caulerpa sertularioides, Padina gymnospora, Sargassum liebmannii [18], U. lactuca, Laminaria spp., P. gymnospora, Durvillaea potatumum, C. sertularioides, S. johnstonii, and S. liebmannii [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seaweed extracts, also known as macroalgae, are considered an important category of non-microbial plant biostimulants due to their use on several agronomic and horticultural crops under both conventional and organic farming systems [34]. Several authors reported that macroalgae such as Ascophyllum nodosum, Ecklonia maxima or Pterocladia capillacea can: (i) improve the agronomic performance of soybean and bean [35,36], potato [37], and Jew's mallow [38]; and (ii) enhance fruit setting in eggplant [39]. In addition to seaweed extracts, the use of PGPR such as Bacillus thuringiensis was also considered an efficient approach to boost yield in a sustainable manner.…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Mormentioning
confidence: 99%